Thermal comfort evaluation of an operating room through CFD methodology - Nelson J. O. Rodrigues (2013)
Although the heating, ventilation and air conditioning systems consume a large amount of energy, they are necessary to provide thermal comfort conditions and good air quality. Specifically in operating rooms, the environmental conditions should be suitable for medical staff performance and patients' safety. This study focuses on the evaluation of the thermal comfort sensation felt by surgeons and nurses, in an orthopaedic surgical room of a Portuguese hospital. Computational fluid dynamic tools were applied for evaluating the predicted mean vote (PMV) index. This enlightened us to the fact that using average ventilation values to calculate the index does not provide a correct and enough descriptive evaluation of the surgical room thermal environment. As reported, surgeons feel slightly hotter than nurses. The nurses feel a slightly cold sensation under the air supply diffuser and their neutral comfort zone is located in the air stagnation zones close to the walls.